Homologs of vertebrate Opn3 potentially serve as a light sensor in nonphotoreceptive tissue - Koyanagi, Mitsumasa (National Academy of Sciences, 2013)
Most opsins selectively bind 11-cis retinal as a chromophore to form a photosensitive pigment, which underlies various physiological functions, such as vision and circadian photoentrainment. Recently, opsin 3 (Opn3), originally called encephalopsin or panopsin, and its homologs were identified in various tissues including brain, eye, and liver in both vertebrates and invertebrates, including human. Because Opn3s are mainly expressed in tissues that are not considered to contain sufficient amounts of 11-cis retinal to form pigments, the photopigment formation ability of Opn3 has been of interest. Here, we report the successful expression of Opn3 homologs, pufferfish teleost multiple tissue opsin (PufTMT) and mosquito Opn3 (MosOpn3) and show that these proteins formed functional photopigments with 11-cis and 9-cis retinals. The PufTMT- and MosOpn3-based pigments have absorption maxima in the blue-to-green region and exhibit a bistable nature. These Opn3 homolog-based pigments activate G(i)-type and G(o)-type G proteins light dependently, indicating that they potentially serve as light-sensitive G(i)/G(o)-coupled receptors. We also demonstrated that mammalian cultured cells transfected with the MosOpn3 or PufTMT became light sensitive without the addition of 11-cis retinal and the photosensitivity retained after the continuous light exposure, showing a reusable pigment formation with retinal endogenously contained in culture medium. Interestingly, we found that the MosOpn3 also acts as a light sensor when constituted with 13-cis retinal, a ubiquitously present retinal isomer. Our findings suggest that homologs of vertebrate Opn3 might function as photoreceptors in various tissues; furthermore, these Opn3s, particularly the mosquito homolog, could provide a promising optogenetic tool for regulating cAMP-related G protein-coupled receptor signalings.